Irregularly Irregular Stellate Incisions for Selective Reduction of Benign Facial Lesions. Issue 7 (7th July 2022) - Teplica, David; Cooney, Emmett; Srock, Jamey; Sayers, Michael
Abstract : Background: Cosmetic outcomes are among patients' top concerns when discussing treatment options for facial nevi. Benign lesions of the face often enlarge with time, and many patients seek care to minimize the perceived deformity. Complete excision remains the frontline treatment for facial lesions, but a choice must be made between the deformity from the lesion itself and scar deformity incurred from its removal. Traditional elliptical excision results in a linear scar that is often conspicuous, while alternatives to surgical excision seek to minimize scarring but possess their own disadvantages. We report a new application for nevus reduction (subtotal or near-total excision) to diminish deformity from the lesion itself while minimizing scar visibility with a novel "irregularly irregular stellate incision" approach. Methods: Incisions are made in a stellate pattern with irregularly irregular borders circumscribed within the lesion. Therefore, the scar is restricted to the lesion surface, while a reduction in area and projection off the skin surface can be tailored to fit the patient's wishes for any benign skin feature. Results: This technique has been employed with hundreds of facial lesions, with two representative cases shown. No significant complications have been observed and the method has been used on a wide variety of sizes and types of lesions. Conclusions: The technique presented meets the need for minimal scarring when reducing benign lesions of the face. The method is applicable to a wide range of presentations and can also function as a method to biopsy lesions, should there be concerns about pathology.